Incidence and factors influencing delayed onset of lactation: a systematic review and meta-analysis - Yijuan Peng; Ke Zhuang; Yan Huang (BMC, 2024)
Abstract Background Breastfeeding has many benefits for mothers and infants. Lactogenesis II is one of the key steps in the implementation of breastfeeding. If lactogenesis II occurs more than 72 h after delivery, it is termed delayed onset of lactation (DOL). DOL is associated with decreased milk production, shortened breastfeeding time, and pathological neonatal weight loss. A comprehensive summary of the incidence and factors influencing DOL is needed to provide a basis for improving breastfeeding practices and health outcomes. Methods Studies on the incidence and factors influencing DOL were retrieved from 13 Chinese and English databases (PubMed, Embase, Web of Science, Cochrane Library, CINAHL, etc.) from database inception to August 2023. Two researchers independently conducted the study screening, data extraction and quality evaluation. Stata 16.0 SE software was used for data analysis, and sensitivity analysis and publication bias tests were also performed. The qualitative description method was used to analyse studies that could not be combined quantitatively. Results A total of 35 studies involving 19,176 parturients, including 4,922 who had DOL, were included. The mean Newcastle‒Ottawa scale score of the included studies was ≥ 6, indicating that the quality was relatively high. Finally, the incidence of DOL was 30%, and 13 factors influencing DOL with robust results and no publication bias were obtained: prepregnancy body mass index (overweight or obesity), gestational diabetes, gestational hypertension, thyroid disease during pregnancy, serum albumin levels (< 35 g/L), parity, (unscheduled) caesarean section, caesarean section history, daily sleep duration, gestational age, birth weight (< 2.5 kg), breastfeeding guidance and daily breastfeeding frequency. However, there were still six influencing factors with undetermined associations: age, gestational weight gain, birth weight (≥ 4 kg), anxiety, time of first breastfeeding session (maternal separation) and breast massage or treatment. Conclusions The incidence of DOL is high. Clinicians should pay attention to parturients at high risk of DOL and formulate targeted prevention strategies according to the influencing factors to reduce the occurrence of DOL and promote better maternal and infant outcomes. Trial registration PROSPERO (ID: CRD42023458786), September 10, 2023.